2004
DOI: 10.1152/ajprenal.00379.2002
|View full text |Cite
|
Sign up to set email alerts
|

Ischemia-reperfusion induces G-CSF gene expression by renal medullary thick ascending limb cells in vivo and in vitro

Abstract: Ischemic acute renal failure involves not only the kidney but also extrarenal organs such as the bone marrow that produces inflammatory cells. By ELISA and RNase protection assays, we now show that renal ischemia-reperfusion increases serum concentrations of granulocyte macrophage colony-stimulating factor (G-CSF) protein and increases both G-CSF mRNA and protein in the ischemic kidney. In situ hybridization localized the increased G-CSF mRNA to tubule cells, including medullary thick ascending limb cells (mTA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 55 publications
2
33
0
Order By: Relevance
“…7 It is known that inflammation is a crucial role in the development of AKI; 6,7,26 systemic inflammation could be secondary to local kidney inflammation 11,12 and systemic inflammation accompanied during AKI. 7,[13][14][15][16][17] Human studies showed that AKI is associated with organ failures and cytokine activation. 27 In addition, the relationship between inflammation and AKI severity is most powerful.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 It is known that inflammation is a crucial role in the development of AKI; 6,7,26 systemic inflammation could be secondary to local kidney inflammation 11,12 and systemic inflammation accompanied during AKI. 7,[13][14][15][16][17] Human studies showed that AKI is associated with organ failures and cytokine activation. 27 In addition, the relationship between inflammation and AKI severity is most powerful.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 There is typically a systemic inflammation during AKI. 5,7,[13][14][15][16][17] Neutrophil-lymphocyte ratio (NLR) is an indicator of systemic inflammation, calculated easily from complete blood count. 18 Some studies showed that NLR is promising marker in predicting bacteremia in patients with emergency medical admissions.…”
Section: Introductionmentioning
confidence: 99%
“…This was subcloned into pDrive cloning Vector (Qiagen PCR Cloning Kit) and S35 labeled sense and antisense probes were prepared. Previously published techniques from our laboratory were used for the in situ hybridiation (44,61). In sections adjacent to those probed for CXCL2 in situ, collecting duct were identified by antibody to aquaphorin 3, and proximal tubules were identified by staining with TRITC-coupled LTA (43).…”
Section: Animals B6ifnarmentioning
confidence: 99%
“…The IL-6 fragment for the in situ probe was amplified from an ischemic kidney cDNA library (11). The details of probe preparation and in situ hybridization were published previously by our group (12). To stain with F4/80 antibody, the kidney sections were deparaffinized, blocked with Protein Block Serum (cat.…”
Section: In Situ Hybridization For Il-6 Mrna and Immunohistology For mentioning
confidence: 99%